Analisis Studi Kelayakan Bisnis Pada Usaha Mikro Kecil dan Menengah (UMKM) Kue Bangkit Kenanga Ditinjau dari Aspek Pemasaran dan Manajemen - Wenny Permata Sari; Obadja, Nathanael Nicholas (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This article discusses “Business Feasibility Study on Kue Bangkit Kenanga Micro, Small and Medium Enterprises (MSMEs) in Terms of Marketing and Management Aspects”. The primary issue raised by this article is whether or not a qualitative research approach would be appropriate for the Kue Bangkit Kenanga . This research is intensive, in-depth, and comprehensive because it is carried out directly on the object. This study aims to determine whether MSMEs in Kue Bangkit Kenanga are a viable business opportunity. The purpose of this study was to determine the business feasibility of Kue Bangkit Kenanga. The results of this study are seen from the marketing aspect in sales targets and marketing mix, an organized aspect of management with managers planning and executing.